Experimental Study of the Collision Zone of a Boundary Layer with a Wall Jet - Barata, Jorge M M (2012)
Laser-Doppler measurements are presented for a highly curved flow resulting from the collision of plane turbulent wall jet with a boundary layer. This configuration can be found in the case of impinging jets of a V/STOL aircraft operating in ground vicinity. The experiments were carried out for boundary layer to wall jet velocity ratio of 0.5. The results include mean and turbulent velocity characteristics of the flow field as well as the characterization of the vorticity. The results revealed the existence of very small recirculation zones located upstream the separation point that co-exist and interact with the very well known VSTOL ground vortex. Copyright © 2009 by the American Institute of Aeronautics and Astronautics, Inc.